Development of a structured undergraduate research experience: Framework and implications. Issue 5 (28th April 2016) - Brown, Anne M.; Lewis, Stephanie N.; Bevan, David R.
Abstract: Participating in undergraduate research can be a pivotal experience for students in life science disciplines. Development of critical thinking skills, in addition to conveying scientific ideas in oral and written formats, is essential to ensuring that students develop a greater understanding of basic scientific knowledge and the research process. Modernizing the current life sciences research environment to accommodate the growing demand by students for experiential learning is needed. By developing and implementing a structured, theory‐based approach to undergraduate research in the life sciences, specifically biochemistry, it has been successfully shown that more students can be provided with a high‐quality, high‐impact research experience. The structure of this approach allowed students to develop novel, independent projects in a computational molecular modeling lab. Students engaged in an experience in which career goals, problem‐solving skills, time management skills, and independence in a research lab were developed. After experiencing this approach to undergraduate research, students reported feeling challenged to think critically and prepared for future career paths. The approach allowed for a progressive learning environment where more undergraduate students could participate in publishable research. Future areas for development include implementation in a bench‐top lab and extension to disciplines beyond biochemistry. In this study, it has been shown that utilizing the structured approach to undergraduate research could allow for more students to experience undergraduate research and develop into more confident, independent life scientists well prepared for graduate schools and professional research environments. © 2016 by The International Union of Biochemistry and Molecular Biology, 44(5):463–474, 2016.